A comprehensive framework for assessing the sustainability of social-ecological landscapes - Atampugre, Gerald; Cofie, Olufunke O.; Mabhaudhi, Tafadzwanashe (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
This Briefing Note proposes a framework for status assessment and performance evaluation of social ecological landscapes. Two important application of this framework is envisaged: (a) It can facilitate inclusive decision-making by multiple stakeholders working in the same landscape by explaining interactions, synergies, and trade-offs among SEL goals and landscape components; and (b) When SEL related bundles of innovations are successful (or otherwise), the framework can help document same, reinforcing the case for (not) adopting and scaling up/out.